Evaluation of skills transfer in human resources: analysis of methodological approaches - Fatiha, BAILLA; NAIT BELAID, Youssef (International Journal of Scientific Research and Innovative Studies, 2025)
The human capital is a key element that form the basis of the organisation's creativity and productivity. Creativity and productivity are well-observed phenomena. These results are due to investment in continuous learning through training, which enables collective cognition and flexibility. The results of these processes are reflected in performance. However, assessing these processes remains complex due to the immaterial nature of knowledge and the social dimension of its dissemination. This article discusses methods that can be used to evaluate management of knowledge and skills. To this end, it is important to identify what we call qualitative and quantitative evaluation systems, analyse their performance indicators, and highlight the main difficulties that can hinder the success of this process. Received Date: July 19, 2025 Accepted Date: August 11, 2025 Published Date: August 30, 2025 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/411